2020
DOI: 10.3389/fimmu.2020.00368
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Pathway Expression in the Skin of Leprosy Patients: Association With Skin and Neural Damage

Abstract: Introduction: Leprosy is an infectious disease caused by Mycobacterium leprae, a debilitating disease that affects the skin and peripheral nerves. It is possible that tissue changes during infection with leprosy are related to alterations in the activity of the Notch signaling pathway, an innate signaling pathway in the physiology of the skin and peripheral nerves. Methods: This is a descriptive observational study. Thirty skin biopsies from leprosy patients and 15 from individuals with no history of this dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Likewise, this finding is consistent and similar to the one reported by our research group on dermal nerves from MB leprosy patients. 5 The IHC results determined that HES-1 could have an efficiency comparable to that of S-100 as an auxiliary immunomarker in diagnosing MB leprosy. However, in PB forms, we observed that HES-1 had a lower sensitivity (66.7%) than S-100 (100%), even though this transcriptional factor is 100% specific in PB and MB leprosy.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Likewise, this finding is consistent and similar to the one reported by our research group on dermal nerves from MB leprosy patients. 5 The IHC results determined that HES-1 could have an efficiency comparable to that of S-100 as an auxiliary immunomarker in diagnosing MB leprosy. However, in PB forms, we observed that HES-1 had a lower sensitivity (66.7%) than S-100 (100%), even though this transcriptional factor is 100% specific in PB and MB leprosy.…”
Section: Discussionmentioning
confidence: 95%
“…5 Besides, this cell dedifferentiation would alter the keratinocytes' innate and adaptative immune response, affecting the antigenic presentation and the differentiation of CD4 + LT toward a Th1 and Th17 pattern. 5 Furthermore, in the eccrine and hair follicle cells, reducing HES-1 would alter the stem cell activity of these cutaneous annexes. 5 Conversely, we propose that these changes in HES-1 expression in PB and MB forms could be explained by a common inflammatory component in all clinical forms of leprosy, possibly related to alterations in the glycosylation of Notch receptors and their interaction mainly with Jagged-type ligands, 5,11 which would reduce the expression of HES-1 in the epidermis and skin appendages of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations